Novel linkage of LMNA Single Nucleotide Polymorphism with Dilated Cardiomyopathy in an Indian case study. (1st June 2015) - Banerjee, Avinanda; Ghoshal, Pradip K.; Sengupta, Kaushik
Abstract: Background: Dilated Cardiomyopathy (DCM) is one of the most commonly encountered heart diseases reported globally. It is characterized by enlarged ventricles with impaired systolic and diastolic functions. Mutations in LMNA gene are one of the causative factors to precipitate the disease. However, association of SNPs of LMNA with DCM in particular has not been well documented. Method: Here we present a limited and restricted case study of patients from south eastern part of India afflicted with idiopathic DCM and conduction defects. By using next generation sequencing we have sequenced the exons of LMNA gene from genomic DNA isolated from patients. Result: We have identified the linkage of 8 different LMNA SNPs with idiopathic DCM viz. rs121117552, rs538089, rs505058, rs4641, rs646840, rs534807, rs80356803 and rs7339. These SNPs are scattered throughout the gene with prevalence for the region encoding the central rod domain of lamin A/C. Conclusion: Most of these SNPs in LMNA were previously reported to be involved in various disorders other than DCM. We conclude that, variation in LMNA is one of the major underlying genetic causes for the pathogenesis of DCM, as observed in few Indian populations.